Financing three decades of development in the Caribbean : 1970-2000 (CDB St. MichaelBB, 2000)
Traces the activities and achievements of the Caribbean Development Bank over the last three decades.
Keywords: INTERGOVERNMENTAL ORGANIZATIONS